Fifteen-Year Single-Center Experience of Biliary Complications in Liver Trauma Patients: Changes in the Management of Posttraumatic Bile Leak - Stonelake, Stephen; Ali, Sana; Pinkey, Benjamin; Ong, Evelyn; Anbarasan, Ravindar; McGuirk, Simon; Perera, Thamera; Mirza, Darius; Muiesan, Paolo; Sharif, Khalid (European Journal of Pediatric Surgery, 2020)
Introduction Management of posttraumatic bile leak has evolved over time in our unit, from endoscopic retrograde cholangiopancreatography (ERCP) stenting to intraperitoneal drainage (IPD) alone as first-line treatment for intraperitoneal bile leak.Materials and Methods Retrospective review of liver trauma patients from 2002 to 2017. Demographics, time and mode of diagnosis of bile leak, management, and outcome were analyzed of the box plot.Results In 118 patients, there were 28 traumatic bile leaks. Eighteen were free intraperitoneal and 10 were localized bilomas. The median time of diagnosis was 6 days following injury. The modes of diagnosis were preemptive hepatobiliary scintigraphy (18), computed tomography (CT) or ultrasound (7), and laparotomy (3). Free intraperitoneal biliary leak management included 11 IPD alone, 3 IPD plus ERCP, 2 IPD plus transcystic biliary stent (TBS), 1 operative cholangiogram, and 1 no intervention. Median time of IPD duration was 7 days (4–95) in IPD alone versus 14 days (6–40) in IPD + ERCP/TBS (p = 0.3). Median inpatient length of stay was 13 days (8–44) in IPD alone versus 12 days (8–22) in IPD + ERCP/TBS (p = 0.4).Conclusion Placement of IPD alone, as first-line treatment, is safe and effective in the management of intraperitoneal bile leaks, avoiding the costs and potential complications of ERCP.
Keywords: bile leak; drain; liver trauma; endoscopic retrograde cholangiopancreatography